The COMT Val158Met polymorphism modulates working memory performance under acute stress - Buckert, Magdalena; Kudielka, Brigitte M.; Reuter, Martin; Fiebach, Christian J. (Psychoneuroendocrinology, 2012)
One of the most widely studied genetic polymorphisms regarding cognitive and emotional phenotypes is the COMT Val158Met polymorphism that influences dopamine availability in the prefrontal cortex (PFC). The PFC is the key brain structure for higher cognitive functions such as working memory, as well as an important regulatory site and target of the psychoendocrine stress response. Dopamine is thought to influence PFC functions in an inverted u-shaped manner. Thus, a stress-related increase in prefrontal dopamine is hypothesized to exert differential effects on working memory performance depending on the genetically determined baseline dopamine level in the PFC. Thirty-three healthy young subjects homozygous for the COMT Val158Met polymorphism were selected from a larger pre-genotyped sample. They performed an n-back working memory task after exposure to a laboratory psychosocial stress induction paradigm (The Trier Social Stress Test for Groups; TSST-G). Under stress, working memory performance of Met homozygotes was significantly worse than working memory performance of Val homozygotes. Importantly, this genotype effect was restricted to the medium difficulty level of the n-back task. Our results demonstrate that working memory performance under stress is influenced by genetic variation in prefrontal dopamine levels. More generally, our results point to the importance of considering the complex interaction of genes, environment, and task variables.